Partitioning of Volatile Halocarbons between Surrogates for Atmospheric Solid Aerosols and Gas Phase as Examined by TPD MS and Inverse Gas Chromatography - Bogillo, V.I.; Bazylevska, M.S.; Mischanchuk, B.G.; Pokrovskiy, V.A. (Хімія, фізика та технологія поверхні, 2010)
The desorption non-isothermal kinetics of preliminary adsorbed Cl, Br, and I-containing volatile halocarbons from the surface of surrogates for atmospheric solid aerosols (fumed silica and alumina, silica gel and H-mordenite) was studied by TPD MS. The TPD spectra demonstrate high heterogeneity of the surface studied. The average desorption activation energies and half-widths of the halocarbons desorption energy rectangular distribution were calculated. The relationships between the average desorption activation energies and molecular descriptors for the halocarbons were derived for the solids. The partitioning of the halocarbons and additional volatile organics between surrogates for mineral and carbonaceous atmospheric aerosols (silica gel, Carbopack S, Carbosil) was examined by using the inverse gas chromatography method. These data indicate to the energetic heterogeneity of the solid surfaces. The average adsorption energies and variances of the adsorption energy rectangular distribution were calculated and connected with molecular descriptors of the volatiles. A relationship is observed between average desorption activation energies of halocarbons on the silica gel surface from TPD MS data and average adsorption energies in these systems determined using inverse gas chromatography method at finite concentrations. Кінетика неізотермичної десорбції попередньо адсорбованих Cl, Br і I-вмістних галогенвуглеводнів (ГВ) з поверхні сурогатів атмосферних твердих аерозолів (пірогенні кремнезем і оксид алюмінію, силікагель і Н-морденіт) вивчена методом температурно-програмованої десорбційної мас-спектрометрії (ТПД МС). ТПД спектри демонструють високу неоднорідність вивчених поверхонь. Розраховані середні величини енергії активації десорбції та півширини прямокутних розподілів енергій десорбції ГВ. Отримані співвідношення між середніми енергіями активації десорбції ГВ і їх молекулярними дескрипторами для всіх вивчених твердих тіл. Розподіл ГВ і додаткових летких органічних сполук між сурогатами мінеральних і вуглецьвмісних атмосферних аерозолів (сілікагель, Карбопак і Карбосіл) досліджено методом оберненої газової хроматографії (ОГХ). Дані ОГХ вказують на енергетичну неоднорідність поверхні цих твердих тіл. Розраховані середні величини енергії адсорбції ГВ і дисперсії прямокутного розподілу поверхонь по енергіям адсорбції та знайдені зв’язки між цими величинами та молекулярними дескрипторами цих летких сполук. Встановлено співвідношення між середніми енергіями активації десорбції ГВ з силікагелю з даних ТПД МС і середніми енергіями адсорбції в цих системах, визначеними з даних ОГХ при скінченних концентраціях. Кинетика неизотермической десорбции предварительно адсорбированных Cl, Br и I-содержащих галогенуглеводородов (ГУ) с поверхности суррогатов атмосферных твердых аэрозолей (пирогенные кремнезем и окись алюминия, силикагель и Н-морденит) изучена методом температурно-программированной десорбционной масс-спектрометрии (ТПД МС). ТПД спектры демонстрируют высокую неоднородность изученных поверхностей. Рассчитаны средние значения энергии активации десорбции и полуширины прямоугольных распределений энергий десорбции ГУ. Получены соотношения между средними величинами энергии активации десорбции ГУ и их молекулярными дескрипторами для всех изученных твердых тел. Распределение ГУ и добавочных летучих органических соединений между суррогатами минеральных и углеродсодержащих атмосферных аэрозолей (силикагель, Карбопак и Карбосил) исследовано методом обращенной газовой хроматографии (ОГХ). Данные ОГХ указывают на энергетическую неоднородность поверхности этих твердых тел. Рассчитаны средние энергиии адсорбции ГУ и дисперсии прямоугольного распределения поверхностей по энергиям адсорбции и найдены связи между этими величинами и молекулярными дескрипторами летучих соединений. Установлено соотношение между средними энергиями активации десорбции ГУ с силикагеля из данных ТПД МС и средними энергиями адсорбции в этих системах, определенными из данных ОГХ при конечных концентрациях.